Are Japanese people satisfied with their health care system and services? Empirical evidence from survey data. Issue 4 (April 2019) - Ii, Masako; Niu, Bing
Highlights: Approximately 17% of respondents were "not sure" about Japan's health care system. Older respondents evaluated the system more favorably then younger respondents. Approximately 26% of respondents had no doctor consultations during the past year. Japanese people lack adequate information to guide their selection of medical institutions. Abstract: Background: Japan's universal health care system provides many advantages for its users, including affordable health coverage with free and equal access to medical institutions. However, the Japanese population's satisfaction with the health care system is among the lowest internationally. This paper investigates the extent and determinants of satisfaction toward Japan's health care system and services, and compares the results with those of eleven other high-income countries. Methods: We collected data from Japanese respondents of a 2014 survey based on the 2010 Commonwealth Fund International Health Policy Survey. We analyzed survey data to explore the determinants of the respondents' overall satisfaction with the health care system, and quantified satisfaction using various dimensions. Results: Almost 17% of respondents were "not sure" of their opinion of Japan's health care system. Overall satisfaction in Japan was much lower than that of other high-income countries. Older respondents (≥65 y) evaluated the system more than twice as favorably as younger respondents. Also, the respondents' overall satisfaction with the health care system was intrinsically related to their assessments of health services actually received. Discussion: The higher satisfaction of older persons may be influenced by their higher care needs and use of health services than younger respondents. The promotion of community-based preventive services involving well-trained professionals may improve the use of health care and increase satisfaction levels.